2019
DOI: 10.1017/s2040174419000783
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effect of anthropometry and physical fitness on the relationship between birthweight and basal metabolic rate in children

Abstract: Background: Birthweight (BW) has been associated with anthropometry, body composition and physical fitness during growth and development of children. However, less is known about the mediation effect of those variables on the relationship between BW and basal metabolic rate (BMR) in children. Objective: To analyse the mediation effect of anthropometry, body composition and physical fitness on the association between BW and BMR in children. Methods: In total, 499 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Data from the present study show a reduction in subcutaneous adiposity folds (peripheral and central) in addition to lean body mass in LBW children. Our results are in line with previous studies carried out with LBW children, where a reduction in the percentage of body fat, fat mass, and BMI was found (FAO/PAHO, 2016; Nobre et al, 2020; Santos et al, 2018; Tzioumis & Adair, 2014). Our findings with Mozambican children fit the pattern of the short‐term adaptive response devised by DOHaD hypothesis which is already well‐known and described in cohort studies in several countries (Tan et al, 2024).…”
Section: Discussionsupporting
confidence: 93%
“…Data from the present study show a reduction in subcutaneous adiposity folds (peripheral and central) in addition to lean body mass in LBW children. Our results are in line with previous studies carried out with LBW children, where a reduction in the percentage of body fat, fat mass, and BMI was found (FAO/PAHO, 2016; Nobre et al, 2020; Santos et al, 2018; Tzioumis & Adair, 2014). Our findings with Mozambican children fit the pattern of the short‐term adaptive response devised by DOHaD hypothesis which is already well‐known and described in cohort studies in several countries (Tan et al, 2024).…”
Section: Discussionsupporting
confidence: 93%
“…As the study analyzed the differences in BMR between physical fitness clusters, both male and female children showed a statistically significant difference, and those in cluster 2 appeared to have the highest BMR. According to preceding research studying how the body and physical fitness affected BMR, involving about 500 children aged between seven and ten, grip strength and power affected BMR in male children, while only the grip strength was an affecting element in female children [58]. This study brought a similar result; the BMR of children in cluster 2, who had high muscular strength and muscular endurance, appeared to be the highest, and those cluster 1 had the lowest.…”
Section: Discussionsupporting
confidence: 61%
“…Low performance and metabolic capacity of skeletal muscles, represented by a reduction in skeletal muscle mass and a low proportion of fast‐twitch muscle fibers, have been associated with low birth weight (Chomtho et al, 2008; Keller et al, 2000; Ortega et al, 2009; Patel et al, 2012; Rogers et al, 2006; Sayer et al, 2004). According to a recent study conducted by Nobre et al (2020), the deficit in the muscle strength observed in children with low birth weight mediated the relationship between birth weight and basal metabolic rate. Moreover, low bone mineral density and impairment of the biomechanical properties of skeletal muscle have also been observed in children with extremely low or low birth weight (Hovi et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that individuals with extremely low (<1000 g), very low (<1500 g), and low (<2500 g) birth weights develop a physical fitness deficit during infancy until adulthood (Burns et al, 2009; Danks et al, 2013; Morrison et al, 2020; Rogers et al, 2005). Despite some inconsistency (Orterga et al, 2009; Salonen et al, 2011), poor physical fitness could be due to deficits in cardiorespiratory endurance and muscle strength (Ahlqvist et al, 2019; Clemm et al, 2012; Dodds et al, 2012; Ferreira et al, 2017; Inskip et al, 2007; Kensara et al, 2005; Moura‐dos‐Santos et al, 2013; Nobre et al, 2020). Therefore, this study aimed to evaluate whether birth weight acts as a prenatal determinant of physical fitness parameters and to determine the role of environmental or biological variables on this effect.…”
Section: Introductionmentioning
confidence: 99%